2003
DOI: 10.1074/jbc.m207470200
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-induced and Age-associated Increase in Macrophage COX-2 Expression Is Mediated through Up-regulation of NF-κB Activity

Abstract: We have shown that the age-associated increase in lipopolysaccharide (LPS)-stimulated macrophages (M) prostaglandin E 2 (PGE 2 ) production is because of ceramide-induced up-regulation of cyclooxygenase (COX)-2 transcription that leads to increased COX-2 expression and enzyme activity. To determine the mechanism of the age-related and ceramide-dependent increase in COX-2 transcription, we investigated the role of various transcription factors involved in COX-2 gene expression. The results showed that LPS-initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 56 publications
1
91
2
1
Order By: Relevance
“…The sphingomyelin pathway and ceramides themselves are reported to play a role in the regulation of IL6 gene expression [11], probably through the activation of transcription factors such as the nuclear factor kappa-B (NFκB) [11,12]. Ceramides can act as inducers of proinflammatory cytokines through the Log value for serum IL-6 (pg/ml) * Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The sphingomyelin pathway and ceramides themselves are reported to play a role in the regulation of IL6 gene expression [11], probably through the activation of transcription factors such as the nuclear factor kappa-B (NFκB) [11,12]. Ceramides can act as inducers of proinflammatory cytokines through the Log value for serum IL-6 (pg/ml) * Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies confirmed that NF-κB signaling pathways modulate COX-2 expression (Kim et al 2012;Wu et al 2003). To validate whether the increased expression of COX-2 in aged mouse peritoneal macrophages is associated with the activation of NF-κB, the level of phosphorylated IκBα (p-IκBα) expression was detected by Western blot assay.…”
Section: Lps Enhances Expression Of Cox-2 and Pge2 In Aged Mouse Perimentioning
confidence: 99%
“…Therefore, there might exist disordered regulation of COX-2 expression in the aging body. Wu et al (2003) demonstrated that NF-κB is a critical positive regulator in the age-associated LPS-induced upregulation of COX-2 activation in macrophages. To confirm this and to also ascertain the role of NF-κB in the age-associated increase of COX-2 expression, we demonstrated that NF-κB activation caused by LPS stimulation in macrophages was mirrored by those in COX-2 expression.…”
Section: Tsa Suppresses Cox-2 Protein Expression By Upregulation Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of the hypothesis that ceramide could play a role as inducer of survival pathways, C2 ceramide was shown to upregulate the expression of antiapoptotic genes such as Bcl-2 and Bcl-w in HC11 mammary epithelial cells 15 and cyclooxygenase (COX-2) in mouse macrophages. 16 Moreover, C2 ceramide-induced expressions of inducible nitric oxide synthase (iNos) in rat primary astrocytes 17 and in rat vascular smooth muscle cells 18 were reported to occur via NF-kB activation. The activation of the transcription factor NF-kB by other apoptotisinducing stimuli such as TNF-a, ionizing radiation or certain chemotherapeutic compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%